Shallow meritocracy: An experiment on fairness views - Peter Andre (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
Meritocracies aspire to reward effort and hard work but promise not to judge individuals by the circumstances they were born into. The choice to work hard is, however, often shaped by circumstances. This study investigates whether people's merit judgments are sensitive to this endogeneity of choice. In a series of incentivized experiments with a large, representative US sample, study participants judge how much money two workers deserve for the effort they exerted. In the treatment condition, unequal circumstances strongly discourage one of the workers from working hard. Nonetheless, I find that individuals hold the disadvantaged worker fully responsible for his choice. They do so, even though they understand that choices are strongly influenced by circumstances. Additional experiments identify the cause of this neglect. In light of an uncertain counterfactual state - what would have happened on a level playing field - participants base their merit judgments on the only reliable evidence they possess: observed effort levels. I confirm these patterns in a structural model of merit views and a vignette study with real-world scenarios.
Keywords: C91; D63; D91; H23; 330; Meritocracy; attitudes toward inequality; redistribution; fairness; responsibility; social preferences; inference; uncertain counterfactual